Characterization and optimization of microwave-assisted extraction of B-phycoerythrin from Porphyridium purpureum using response surface methodology and Doehlert design. (September 2022) - Huschek, Gerd; Rawel, Harshadrai M.; Schweikert, Torsten; Henkel-Oberländer, Janin; Sagu, Sorel Tchewonpi
Abstract: Microalgae are one of the most promising food source of the future. Nowadays, extracts of high-value active substances of biomass are business aims for the development of food additives in personalized nutrition, in cosmetics and pharmaceuticals. A new-patented vertical farming cultivation technology was used for production of Porphyridium purpureum . In this work, microwave assisted extraction was used to extract B-phycoerythrin from Porphyridium purpureum biomass. Response surface methodology was implemented for optimization. Numerical optimization established the best point of the experimental domain (biomass/solvent of 16.8 mg/mL, time of 172 s, and temperature of 30 °C) with a desirability value of 0.82. Corresponding experimental responses values of 7.2 mg, 8.5 % and 13, 961 PA/μg biomass were obtained for extracted proteins, extraction yield and extracted B-phycoerythrin, respectively. Final freeze-dried product indicated protein content of 55 % using Kjeldahl while targeted mass spectrometry analysis revealed that B-phycoerythrin represented 93 % of the total protein. Graphical abstract: Unlabelled Image Highlights: A new-patented cultivation technology used for production of Porphyridium purpureum . Optimum conditions of the microwave-assisted extraction were determined. Purification of B-phycoerythrin through HCl precipitation was found to be effective. Final product was successfully characterized thanks the developed LC-MS/MS method. Solubility assessment in distilled water and buffers was furthermore performed.